Astrocyte-mediated metaplasticity in the hippocampus: Help or hindrance?. (19th November 2015) - Jones, O.D.
Highlights: Synaptic plasticity is critical for healthy cognition and is profoundly affected by disease. Synaptic plasticity mechanisms are regulated by prior neural activity (metaplasticity). Astrocytes may mediate certain forms of metaplasticity. Astrocytes display altered form and function in many pathologies common to the hippocampus. Astrocyte-mediated metaplasticity may be inhibited or unduly engaged in injury or disease and contribute to pathology. Abstract: For over two decades it has been increasingly appreciated that synaptic plasticity mechanisms are subject to activity-dependent metaplastic regulation. In recent years it has also become apparent that astrocytes are active partners with neurons at synapses, and have the capability to powerfully regulate synaptic plasticity. However, the field of astrocyte-mediated metaplasticity is still very much in its infancy. Further, what contribution astrocyte-mediated metaplasticity makes to hippocampal dysfunction is almost entirely unknown. This contribution may be particularly important given that altered plasticity in the hippocampus is a hallmark of several disease states. The known ways by which astrocytes exert metaplasticity are reviewed here, and hypothetical mechanisms of astrocyte-mediated metaplasticity are considered for the benefit of future investigation. The latter half of this review focuses on what part these mechanisms, and others, may play in the diseased or injured hippocampus, and how this might contribute to the altered cognition seen in several pathologies common to the hippocampus.